Entrepreneurship Challenges and Capacity Building Needs in Local Tourism Development (A Study of the Sumber Maron Tourism Area, Malang Regency, Indonesia) - Rudianto; Arif Efendi; Bagus Pramudia Ananta; Kholid (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2026)
Purpose: Community based tourism development requires the active participation of local communities as tourism entrepreneurs. However, in many natural tourist destinations, the entrepreneurial readiness of local communities is still limited. This study aims to analyze entrepreneurial challenges and capacity building needs and examine their impact on entrepreneurial readiness among prospective tourism entrepreneurs in the Sumber Maron tourist area, Pagelaran District, Malang Regency. Method: This study uses a quantitative approach with a survey of 85–100 prospective local tourism entrepreneurs. Data were collected through a structured questionnaire using a Likert scale and analyzed using descriptive statistics, correlation analysis, and multiple linear regression. Result: The results show that entrepreneurial challenges have a negative effect on entrepreneurial readiness, while capacity building needs have a positive and significant effect. These results highlight the importance of designing evidence-based and contextual entrepreneurship development programs to enhance sustainable local tourism development. Contribution: A contextually designed entrepreneurship development program is expected to comprehensively enhance the capacity of prospective tourism entrepreneurs, from business planning and operational management to marketing and tourism product innovation. With the right and sustainable approach, strengthening entrepreneurial readiness will not only encourage the growth of local tourism businesses but also contribute to the development of Sumber Maron as an inclusive and sustainable tourism destination